2017
DOI: 10.1080/14756366.2016.1265517
|View full text |Cite
|
Sign up to set email alerts
|

Design of potent fluoro-substituted chalcones as antimicrobial agents

Abstract: Owing to ever-increasing bacterial and fungal drug resistance, we attempted to develop novel antitubercular and antimicrobial agents. For this purpose, we developed some new fluorine-substituted chalcone analogs (3, 4, 9–15, and 20–23) using a structure–activity relationship approach. Target compounds were evaluated for their antitubercular efficacy against Mycobacterium tuberculosis H37Rv and antimicrobial activity against five common pathogenic bacterial and three common fungal strains. Three derivatives (3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 13 publications
0
22
0
Order By: Relevance
“…The research further revealed that fluorinated chalcones with fluoro-substitution in position 2 and or position 5 of its B ring showed higher antibacterial potency against S. aureus, S. pyogenes, E. feacalis, E. coli, P. aeruginosa and antifungal activity against C. albicans, C. glabrata and C. parapsilosis. However, the presence of hydroxyl group on the A ring decreases the antitubercular activity of theses fluorinated chalcones [18]. Also, fluorinated chalcones-1,2,3-triazoles conjugates have been reported to show significant activity against some bacterial and fungal strains [19].…”
Section: Antibacterial Evaluationmentioning
confidence: 99%
“…The research further revealed that fluorinated chalcones with fluoro-substitution in position 2 and or position 5 of its B ring showed higher antibacterial potency against S. aureus, S. pyogenes, E. feacalis, E. coli, P. aeruginosa and antifungal activity against C. albicans, C. glabrata and C. parapsilosis. However, the presence of hydroxyl group on the A ring decreases the antitubercular activity of theses fluorinated chalcones [18]. Also, fluorinated chalcones-1,2,3-triazoles conjugates have been reported to show significant activity against some bacterial and fungal strains [19].…”
Section: Antibacterial Evaluationmentioning
confidence: 99%
“…In their paper, Thasneem and co-workers concluded that chalcone 91 with NH 2 and NO 2 showed excellent activity against Staphylococcus aureus (ATCC5922) and Escherichia coli (ATCC6633) respectively whereas OH showed excellent activity against Saccharomyces cerevisiae [33]. In another paper, compounds 92 with substituents H, 2-F, and 2,5-diF displayed activities against the S. aureus, S. pyogenes, E. faecalis, E. coli, and P. aeruginosa while 92 substituent H and compound 93 were active against tested C. albicans [34]. The presence of halogens in chalcone 94 increases microbial susceptibility [35].…”
Section: Anti-microbial Activitiesmentioning
confidence: 99%
“…Alam et al evaluated heterocyclic chalcones 101 for anti-tubercular activity [37], while, Solankee and Tailor found chalcone 102 to exhibit promising activity [38], In another work, compound 103 with trimethoxy on ring A and fluoro groups on the B showed enhance activity with IC 50 (≤16,760) against Mycobacterium tuberculosis H37Rv compared to the standard drugs Ethambutol (EMB) and Isoniazid (INH) [34] ( Fig. 7).…”
Section: Anti-tubercular (Tb) Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Burmaoglu et al reported antimicrobial activity of fluoro-substituted chalcones (8) and (9) against S. aureus, S. pyogenes, E. faecalis, E. coli, and P. aeruginosa bacteria and C. albicans, C. glabrata, and C. parapsilosis fungal strains. Some of the tested compounds also exhibited antitubercular activity against Mycobacterium tuberculosis [13].…”
Section: Introductionmentioning
confidence: 96%